Rod Bipolar Cells Require Horizontal Cells for Invagination Into the Terminals of Rod Photoreceptors - Nemitz, Lena; Dedek, Karin; Janssen-Bienhold, Ulrike (Frontiers in Cellular Neuroscience, 2019)
In the central nervous system, neuronal processing relies on the precisely orchestrated formation of synapses during development. The first synapse of the visual system is a triad synapse, comprising photoreceptors, horizontal cells and bipolar cells. During the second postnatal week, the axon terminal processes of horizontal cells invaginate rod spherules, followed by rod bipolar cell dendrites. Both elements finally oppose the synaptic ribbon (the release site of glutamate). However, it has not been fully elucidated whether horizontal cells are essential for rod bipolar cell dendrites to find their way into the rod terminal. In the present study, we investigated this question by specifically ablating horizontal cells from the early postnatal mouse retina. We monitored the formation of the rod-to-rod bipolar cell synapse during retinal maturation until postnatal day 21. Based on quantitative electron microscopy, we found that without horizontal cells, the dendrites of rod bipolar cells never entered rod terminals. Furthermore, rods displayed significantly fewer and shorter presynaptic ribbons, suggesting that glutamate release is decreased, which coincided with significantly reduced expression of postsynaptic proteins (mGluR6, GPR179) in rod bipolar cells. Collectively, our findings uncover that horizontal cells are indeed necessary guideposts for rod bipolar cells. Whether horizontal cells release diffusible guidance cues or provide structural guidance by expressing specific cell adhesion molecules remains to be seen.